Home environmental factors as predictors of sexual abuse among school adolescents in Ibadan North local government (2022)
Rape among adolescents has becoming reoccurring and a major public worries with associated health, psychological, and social consequences. The study examined home environmental factors as predictors of sexual abuse among selected post primary students in Ibadan. This paper utilized a descriptive survey research design. The total respondents comprise 300 students randomly selected from selected secondary schools. A questionnaire tagged “Home Environmental Factors as Predictions of Sexual Abuse among School Adolescents The instrument was pre-tested in another school to ascertain the reliability of the instrument while the instrument was validated by experts from a related discipline. Pearson Product Moment Correlation Coefficient at 0.05level of significance was utilised in data analysis. Results indicated that there was a significant links between the home and sexual abuse among school adolescents (r = 0.544, N = 300, P < 0.05), there was a significant connection between the environment and sexual abuse among school adolescents (r = 0.466, N = 300, P< 0.05). Finally, there was significant negative effects of sexual abuse among school adolescents (r = 0.505, N = 300, P < 0.05). This paper recommended that stakeholders should inculcate decent dressing for their wards while moral and religion education should be inculcated.